2020
DOI: 10.1111/ijfs.14653
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of melanoidins derived from Brewers' spent grain: new insights into their structure and antioxidant activity

Abstract: Melanoidins, formed at the final stages of Maillard reaction (MR), present important physiological activities, but their structure and reaction pathways are largely unknown in real food systems. In the present work, these bioactive compounds derived from Brewers' spent grain (BSG) with different roasting degrees were analysed. Results showed that BSG could be considered a more important source of bioavailable antioxidants than what it was reported in previous studies. During MR development, proteinic structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…Besides protein content, significant differences (p < 0.05) were also shown in fat and carbohydrate contents. BSG fat content from BSG was noted for its potential as a source of antioxidants, fatty acids, and volatile tocotrienol compounds ( Bohnsack et al., 2011 ; del Río et al., 2013 ; Fărcaş et al., 2015 ; Parekh et al., 2017 ; Patel et al., 2018 ; Patrignani and González-Forte, 2020 ; Ribau Teixeira et al., 2020 ). The carbohydrate content roughly describes the fiber amount.…”
Section: Resultsmentioning
confidence: 99%
“…Besides protein content, significant differences (p < 0.05) were also shown in fat and carbohydrate contents. BSG fat content from BSG was noted for its potential as a source of antioxidants, fatty acids, and volatile tocotrienol compounds ( Bohnsack et al., 2011 ; del Río et al., 2013 ; Fărcaş et al., 2015 ; Parekh et al., 2017 ; Patel et al., 2018 ; Patrignani and González-Forte, 2020 ; Ribau Teixeira et al., 2020 ). The carbohydrate content roughly describes the fiber amount.…”
Section: Resultsmentioning
confidence: 99%
“…Along with phenolic compounds, the BSG extracts' antioxidant activity has been attributed to a synergic action of melanoidin compounds produced in the malting Maillard reaction, heightening the interest for their co-extraction. In the specific topic of the application of green recovery methods on BSG, coupled melanoidin extraction has been documented by Patrignani and González-Forte (2021), where the application of a microwave treatment was attributed as a promoter of Maillard reaction-derived products and the enhanced antioxidant activity of microwave-treated extracts was associated to a coupling of phenolic acid and melanoidin effects. On another reported green pre-treatment, Kumari et al (2019) applied a pulsed electric field technology on light and dark BSG to enhance the extraction of bioactive compounds.…”
Section: Phenolic Extraction Methods Applied For Bsgmentioning
confidence: 99%
“…The presence of NFC may have an impact on the antioxidant activity of BSG as well. The analysis of bioactive compounds derived from BSG with different roasting degrees revealed that while the Maillard reaction continues the development of melanoidins increases, the antioxidant activity rises and phenolic compounds are bound to the melanoidin structure (Patrignani & González‐Forte, 2021). It can also be observed that the content of lipids and ash significantly decreased ( p < .05) in the protein concentrate, which can be explained by the extraction method.…”
Section: Resultsmentioning
confidence: 99%